Fe2O3 supported Pt single atom catalysts for the selective hydrogenation of cinnamaldehyde. Issue 40 (7th October 2022) - Lan, Huanshi; Qin, Zuzeng; Shi, Shaolin; Zhang, Xingcong; He, Xiaohui; Ji, Hongbing
Abstract : A simple ball milling method was adopted to prepare single atom catalysts with excellent catalytic properties. Abstract : Atomically dispersed Pt species supported on Fe2 O3 (Pt1 /Fe2 O3 ) are successfully constructed by a simple ball milling process. In the selective hydrogenation of cinnamaldehyde (CAL), Pt1 /Fe2 O3 achieves an excellent cinnamyl alcohol (COL) selectivity of 81.7% at a CAL conversion of 91.2% in pure water medium due to the superior dissociation ability of H2 and preferential adsorption of CAL via CO.